Evaluation of Childhood Hypertension in School Going Children Attending Pediatrics OPD in Ghaziabad City (Journal of Pharmaceutical Negative Results, 2022)
Introduction - The purpose of this research was to examine the incidence of hypertension and other forms of high blood pressure in school-aged children who visited the Pediatrics Outpatient Department of a tertiary hospital in a tier II city in Northern India.Materials and methods - We used a cross-sectional observational study with school-aged children who visited the Paediatrics Outpatient Department at SMC to determine the prevalence of asthma in these patients. Information like as ages, sex, medical histories, and smoking habits of parents were recorded. A questionnaire and the 24-hour recall method were used to assess dietary patterns such junk food consumption, fruit consumption, and daily calorie intake. The stadiometer and electronic scale were used to measure height and weight, respectively, while the subjects were clad only in light clothing and without shoes.Results- The findings showed that 9.4% and 6.8% of the respondents, respectively, had elevated blood pressure (BP 90th percentile for age, height, and sex) and hypertension (BP 95th percentile for age, height, and sex). Family history, stress, and insufficient daily physical activity all played key roles in the development of hypertension. A higher body mass index (BMI), greater height, and greater age were all linked to both illnesses.Conclusions- Nine percent and six point eight percent of children ages 6 through 12 were reported to have high blood pressure and hypertension, respectively. These were linked to factors like personal history, life pressure, and sedentary lifestyle.